The Frequency Of Hematological Abnormalities in Children (Age 1 Month To 12 Years) Presenting With Sars-Cov-2 Infection At Shifa International Hospital - Sidra Tul Muntaha; Hammad Ayaz; Huma Mahmood; Afifa Kulsoom; Muhammad Tayyab; Arslan Farooq (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of haematological abnormalities in pediatric patients presenting with COVID-19 infection.